High-Antimicrobial Gallium-Doped Zinc Oxide Thin Films on Bio-Based Poly(Ethylene Furanoate) Substrates for Food Packaging Application - Chaoting Zhu; Danling Ye; Tianqi Zhou; Yashuang Cui; Jianbing Yin (Membranes, 2023)
Thin films of gallium-doped zinc oxide (GZO), with a thickness of around fifty nanometers were deposited on bio-based poly(ethylene furanoate) (PEF) substrates by radio-frequency sputtering. By optimizing the Ga concentration in the target, the optics, water vapor barrier and antibacterial properties of PEF/GZO composite films can be adjusted. The highest visible light transmittance of the samples was around 85.1%. Furthermore, by introducing some GZO films with typical concentrations, the water vapor barrier and antibacterial properties of PEF films were improved. The optimized water vapor permeability of PEF/GZO composite film was 5.3 × 10−12 g·m/m2·s·Pa, and the highest antibacterial rate can reach 99.85% after 4 h. By XPS analysis, the antibacterial mechanism in the samples is envisaged to be mainly due cytotoxicity of Ga ions. The above results indicate that PEF/GZO films have great potential in the field of antibacterial food packaging.